Processamento auditivo temporal em crianças com desvios fonológicos - Marchetti, Paula Tavares (2016)
This study aims to Thirty-six children, that fit the selction criteria, selected through interviews and speech, language and hearing screening have been evaluated. The children who were aged between 6 and 8 years and 18 with normal language development (control group) and 18 with phonological disorders (study group). All the participants have been through phonological evaluation and temporal processing assessments. Among these 18 children with phonological disorders, six have been randomly selected for the study of the therapeutic models used. Among these six, three children have been through auditory training therapy, and the three others, auditory training therapy associated to a specific software-assisted auditory training. As general results, there were statistically significant differences with higher performances of the control group participants compared to the ones in the study group in all temporal processing applied tests. The correlations between the phonological assessment (PCC-R, MICT, altered features numbers, altered phonemes numbers and altered distinctive features) and the temporal processing results were not statistically significant at all. Regarding the comparison of the therapeutic models, there was a improvement in all the participants performance. However, there was no significant difference between the models used. It is concluded that children with phonological disorders have difficulty in auditory temporal processing, but there were not proved correlations between phonology data. Similarly, it was not verified that the computer-assisted auditory training enhances speech, language and hearing therapy of children with phonological disorders.